2011
DOI: 10.1111/j.1600-0463.2011.02838.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear expression of S‐phase kinase–associated protein 2 predicts poor prognosis of hepatocellular carcinoma

Abstract: The S-phase kinase-associated protein 2 (Skp2), which ubiquitinates the cell cycle inhibitor p27(Kip1) and targets it for degradation, is commonly overexpressed in human cancers and is associated with poor prognosis in several cancers. The aim of this study was to investigate Skp2 expression and its clinicopathologic significance in surgically resected hepatocellular carcinomas. We collected 359 hepatocellular carcinoma samples and evaluated Skp2 protein expression in cytoplasmic and nuclear fractions by immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Emerging evidence has demonstrated that Skp2 serves a critical role in the development of liver cancer. For example, the nuclear expression of Skp2 predicted poor prognosis in patients with liver carcinoma (22). In addition, the inhibition of Skp2 induced apoptosis and inhibited cell proliferation in liver carcinoma cells via the upregulation of cyclin dependent kinase inhibitor 1B (p27) (23).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has demonstrated that Skp2 serves a critical role in the development of liver cancer. For example, the nuclear expression of Skp2 predicted poor prognosis in patients with liver carcinoma (22). In addition, the inhibition of Skp2 induced apoptosis and inhibited cell proliferation in liver carcinoma cells via the upregulation of cyclin dependent kinase inhibitor 1B (p27) (23).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed Skp2 is found to be overexpressed in oral squamous cell carcinoma and ER‐negative breast carcinoma . Recent studies suggest that Skp2 is also upregulated in hepatocellular carcinoma and is linked to poor prognosis . (Also refer to Table for other SCF ubiquitin ligases)…”
Section: Ubiquitin Ligases Targeting P53mentioning
confidence: 99%
“…Such an imbalance leads to pRB hyperphosphorylation and rise in E2F1-DP1 complexes, which activate DNA synthesis genes and allow the transition from the G1 to the S phase of the cell cycle in these lesions [ 4 - 8 ]. Although gene silencing by promoter hypermethylation seems to play a major role in the inactivation of tumor suppressor genes in liver cancer [ 9 - 11 ], emerging evidence indicates a post-transcriptional regulation of cell cycle negative modulators by the S-phase kinase-associated protein 1 (SKP1)/CUL1/F-box protein (SCF) complex, an ubiquitin ligase implicated in the G1-S transition regulation, in this tumor type [ 12 - 15 ]. The pro-oncogenic activity of the SCF complex in various tumors, including HCC, seems to reside in its ability to induce the proteasomal degradation of several inhibitors of the cell cycle, including p27 KIP1 , p57 KIP2 , DUSP1, and RASSF1A [ 16 - 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, S-phase kinase-associated protein 2 (SKP2), a main member of the SCF complex, is almost ubiquitously overexpressed in cancer and considered to be a bona fide oncogene due to its transforming abilities in vitro and in vivo [ 16 - 21 ]. Previously, others and we have demonstrated that SKP2 is upregulated in rodent and human HCC [ 12 - 15 ]. In addition, it has been shown that SKP2 nuclear accumulation directly correlates with clinical aggressiveness of HCC and is associated with shorter survival of liver cancer patients [ 15 ].…”
Section: Introductionmentioning
confidence: 99%